Potensi Pengembangan Utilitas Wilayah Kumuh Di Kelurahan Muara Fajar Kota Pekanbaru - Lusi Dwi Putri (Center for Research and Community Service (LPPM) University of Abulyatama, 2018)
Muara Fajar Urban Village is the location of Final Disposal (TPA) for garbage in Pekanbaru City, which if not get special attention can be turned into a very dangerous slum area. This research aims to produce a direction of arrangement of settlement infrastructure of Muara Fajar Urban Village as one of reference for related parties either Local Government or another private party in trying Pekanbaru free of the slum. The method used in determining the potential of utility development in Muara Fajar Village is by analyzing secondary data and primary data through the use of questionnaires and interviews and field observation. The result of requirement analysis of public service means that the potential of settlement utility development which becomes a priority in Muara Fajar Urban Village is drinking water service, wastewater management, environmental drainage and waste management.